Estimation des pluies exceptionnelles journalieres en zone tropicale: cas du bassin versant de l’Oueme au Bénin par comparaison des lois de Jenkinsson et de Gumbel - BACHAROU, Taofic; ADJIBOICHA, Moudachirou; ADJOVI, Edmond C.; ORLOVAa, Elena A; HOUINOU, GOSSOU (My University, 2013)
The present work has for objective the survey of the features of the rainfall observed on the Ouémé's basin and the establishment of the the evaluation of the daily exceptional rains very used in the conception of the hydraulic works and Civil Engineering. The extreme annual daily rainfalls of 37 rainfall stations of Benin installed on the Ouémé's basin have been analyzed on the period 1971-2010. Then, they have been adjusted to an extreme value law selected among the laws of Jenkinson and Gumbel according to the Kolmogorov-Smirnov test. These tests permitted to regionalize the laws of adjustment in distinct two zones of application: the law of Jenkinson appears more adequate to the zone South while the law of Gumbel suits the North zone of Benin better; what makes notice the non consistency of the exclusive use of the law of Gumbel at the time of the studies of conception of hydraulic works on the whole territory. The evaluation of the quantiles relative of daily rain to the period’s back 2, 5, 10, 20, 50 and 100 years revealed that the maximal heights of water of rare frequency are observed at the Cotonou-Airport station on the Coastline and the maximal heights of water weakest in Ina's region to the North of Benin.
Keywords: basin; rain; intensity; duration; frequency; curves